Arbitration in China : a legal and cultural analysis - Fan, Kun. (London : Hart Publishing, 2013)
Written for international businessmen, lawyers, academics and students, this book gives the reader a unique insight into real arbitration practice in China, based on a combination of theoretical analysis and practical insights.
Overview of the Chinese legal framework and arbitration system -- Arbitration agreement -- Arbitral tribunal -- Recognition and enforcement of arbitral awards -- The practice of arbitration institutions -- The combination of mediation with arbitration -- Chinese characteristics in arbitration law and practice -- Traditional legal culture and its influence on contemporary arbitration practice -- The modernization of law and cultural influences on arbitration practice -- Conclusion.
eBooks on EBSCOhost
Keywords: Arbitration and award -- China; Dispute resolution (Law) -- China; Mediation -- China; Règlement de conflits -- Chine; Médiation -- Chine; Arbitrage (Droit) -- Chine; International arbitration; Law -- Arbitration, Negotiation, Mediation; Arbitration and award; Dispute resolution (Law); Mediation; China